The Public Role of Religion and the Response of Public Theology - Kim, Seung-Hwan (Religions, 2024)
This study discusses theological assertions concerning the public role of religion in post-secular societies. In the context of religion’s renewed emergence in the public sphere, it is being called upon to overcome the beliefs of individual and private realms and actively assume the role of a participant in the common goal of a better society. Religion, in this context, is not confined to the personal sphere but is recognized as a crucial participant in shaping a more desirable societal landscape. Religion holds the potential to renew the spirituality of citizens, foster a sense of belonging, and contribute to the formation of social ethics. In response to these circumstances, Christianity is engaging with a new theological methodology known as public theology, proposing a public role for the church and advocating for the public participation of Christians. This study aims to propose public roles for the church and theology in post-secular societies.